2016
DOI: 10.1186/s12986-016-0111-0
|View full text |Cite
|
Sign up to set email alerts
|

2-amino-1-methyl-6-phenylimidazo(4,5-b) pyridine (PhIP) induces gene expression changes in JAK/STAT and MAPK pathways related to inflammation, diabetes and cancer

Abstract: Background2-amino-1-methyl-6-phenylimidazo(4,5-b)pyridine (PhIP), a heterocyclic aromatic amine (HCA) formed in meat that is cooked at high temperatures and then ingested, can potentially be retained in human adipose tissues.MethodsTo determine if PhIP is bioactive in the adipocyte, we exposed a human adipocyte cell line,HepG2 and Caco-2 cells to low dose PhIP. Uptake and retention of PhIP was determined and cytotoxicity was assessed by the TUNEL assay. Relative expression of PhIP-activating genes (CYP1A1, CYP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 45 publications
(39 reference statements)
0
11
0
Order By: Relevance
“…Although the exact mechanisms underlying the observed associations remain unknown, some studies have suggested that certain hazardous chemicals including HAAs, PAHs, nitrosamines, and AGEs, which are produced during hightemperature cooking of meats, might be involved in the development of diabetes (14,16,19). A recent in vitro study by Rogers et al (16) demonstrated that low-dose HAA exposure could induce gene expression changes in JAK/STAT and MAPK pathways linked with inflammation and diabetes.…”
Section: Potential Biological Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the exact mechanisms underlying the observed associations remain unknown, some studies have suggested that certain hazardous chemicals including HAAs, PAHs, nitrosamines, and AGEs, which are produced during hightemperature cooking of meats, might be involved in the development of diabetes (14,16,19). A recent in vitro study by Rogers et al (16) demonstrated that low-dose HAA exposure could induce gene expression changes in JAK/STAT and MAPK pathways linked with inflammation and diabetes.…”
Section: Potential Biological Mechanismsmentioning
confidence: 99%
“…Moreover, accumulating evidence has suggested that cooking meats at high temperature can produce several hazardous chemicals, including heterocyclic aromatic amines (HAAs), polycyclic aromatic hydrocarbons (PAHs), and advanced glycation end products (AGEs) (12)(13)(14), which are known carcinogens or can impact inflammation and insulin sensitivity (15)(16)(17)(18)(19). Cooking temperature, duration, and doneness level can significantly affect the levels of these chemicals in cooked meats (12)(13)(14).…”
mentioning
confidence: 99%
“…This might be caused by cell type-dependent toxic effects of PhIP. A previous report proved this phenomenon based on genotoxic DNA fragmentation by comparing cytotoxicities between carcinoma cells (HepG2 and Caco2 cells) and normal adipocytes 26 . On the other hand, remarkable cytotoxic effects could not be seen in particulate PhIP and PhIP@OA samples even after the 48-h incubation.…”
Section: Resultsmentioning
confidence: 78%
“…VEGFA was found to contribute to increasing adiposity in Iberian pig [ 37 ]. According to the report, EGR1 was down-regulated via c-Fos in mature adipocytes [ 38 ]. CACNB1 gene was reported associated with growth in chicken [ 39 ].…”
Section: Discussionmentioning
confidence: 99%